PENGEMBANGAN PROJECT BOOK UNTUK KETERAMPILAN MENULIS PARAGRAF SEDERHANA SISWA KELAS II SDN KEBON BARU 07 PAGI JAKARTA SELATAN - Putri Aulianti Firdausi; Rudi Ritonga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study purpose to develop a gamification-based Project Book learning media to improve the ability to write simple paragraphs for second-grade students at SDN Kebon Baru 07 Pagi, Jakarta Selatan. This research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 31 students in class IIA. Data collection instruments included expert validation, student and teacher response questionnaires, as well as pre-test and post-test to assess the improvement in writing skills. The results indicated that the developed Project Book is feasible to use, with expert validation scores of 92% for media experts and 94.28% for content experts. The N-gain test results showed that 18 students (58%) achieved high improvement, 13 students (42%) achieved moderate improvement, and no student was in the low category. These findings demonstrate that the Project Book is effective in enhancing second-grade students’ ability to write simple paragraphs.